2022
DOI: 10.1186/s12884-022-04532-2
|View full text |Cite
|
Sign up to set email alerts
|

IVF/ICSI outcomes of euthyroid infertile women with thyroid autoimmunity: does treatment with aspirin plus prednisone matter?

Abstract: Background Thyroid autoimmunity (TAI) has been demonstrated to be associated with adverse pregnancy including recurrent miscarriage, unexplained infertility, and implantation failure. To settle with the fertility problem, prescribing aspirin combined with prednisone (P + A) to women positive for anti-thyroid antibodies is frequent in clinical practice, but the underlying effect remains controversial. Methods A multicenter, retrospective study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, combination therapy with prednisolone enhances clinical pregnancy rates and reduces miscarriage rates in women with TAI undergoing IVF ( 50 ). However, a study involving women with TAI who underwent IVF/ICSI indicated that adjunctive therapy with aspirin and prednisone after embryo transfer may not be necessary for fresh or frozen embryos ( 51 ). This finding demonstrates that targeted pharmacological interventions may prove advantageous in improving reproductive outcomes among patients with TAI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, combination therapy with prednisolone enhances clinical pregnancy rates and reduces miscarriage rates in women with TAI undergoing IVF ( 50 ). However, a study involving women with TAI who underwent IVF/ICSI indicated that adjunctive therapy with aspirin and prednisone after embryo transfer may not be necessary for fresh or frozen embryos ( 51 ). This finding demonstrates that targeted pharmacological interventions may prove advantageous in improving reproductive outcomes among patients with TAI.…”
Section: Discussionmentioning
confidence: 99%
“…also confirmed that LT 4 treatment did not reduce miscarriage rates or increase live birth rates in women undergoing in vitro fertilization embryo transfer (IVF-ET) with intact thyroid function and positive TPOAb ( Wang et al., 2017 ). The use of glucocorticoids and aspirin as adjunctive therapies in euthyroid women with AITD undergoing IVF-ET may not improve pregnancy or live birth rates either ( Zhou et al., 2022 ).…”
Section: The Impact Of Aitd On Pregnancymentioning
confidence: 99%
“…2,6 Treatment of fertilization problems caused by thyroid disorders and thyroid autoimmune diseases that reduce thyroid reserve and lead to in vitro fertilization (IVF) cycle failures have been the focus of many studies on this topic. [7][8][9][10] Immunological factors are essential in fertilization, implantation, and placental development, and infertility has been associated with thyroid autoimmunity. 6,[11][12][13] In infertile women, hypothyroidism is observed in 2% to 4% of cases compared to other populations, and up to twofold more thyroid autoantibodies were found in the infertile group than in the control patients (14% vs. 8%).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of fertilization problems caused by thyroid disorders and thyroid autoimmune diseases that reduce thyroid reserve and lead to in vitro fertilization (IVF) cycle failures have been the focus of many studies on this topic 7–10 . Immunological factors are essential in fertilization, implantation, and placental development, and infertility has been associated with thyroid autoimmunity 6,11–13 .…”
Section: Introductionmentioning
confidence: 99%